2017
DOI: 10.1038/srep46246
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibiting OCT4 and AKT potently suppresses the propagation of human cancer cells

Abstract: AKT serves as an epigenetic modulator that links epigenetic regulation to cell survival and proliferation while the epigenetic mediator OCT4 critically controls stem cell pluripotency and self-renewal. Emerging evidence indicated their complicated interplays in cancer cells and cancer stem cells (CSCs), and inhibiting either one may activate the other. Thus, in this study, we propose a strategy to targeting both factors simultaneously. Firstly, a combination of an OCT4-specific shRNA and the specific AKT inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…We then examined OCT4A protein in the above cells by regular western blotting (WB) analysis using a rabbit monoclonal antibody presumed to be OCT4A-specific (CST 2890). Similar to previous results from our own group 25 , 28 , 29 and other groups 30 32 , we detected two major bands with apparent molecular size of 50 kDa (blue arrow, Fig. 2a ) and 43 kDa (black arrow, Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We then examined OCT4A protein in the above cells by regular western blotting (WB) analysis using a rabbit monoclonal antibody presumed to be OCT4A-specific (CST 2890). Similar to previous results from our own group 25 , 28 , 29 and other groups 30 32 , we detected two major bands with apparent molecular size of 50 kDa (blue arrow, Fig. 2a ) and 43 kDa (black arrow, Fig.…”
Section: Resultssupporting
confidence: 92%
“…We then asked if OCT4A plays a definitive role in anticancer drug resistance, as multiple studies have indicated its involvement in promoting cellular resistance to chemotherapy based on RNAi strategies that were not specifically targeting OCT4A 25 , 29 , 43 , 44 . We treated the WT and OCT4A-KO cells with Cisplatin, a first-line anticancer drug for cervical carcinoma, or Akti-1/2, a potent anticancer agent in clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“… 22 23 24 25 Secondly, OCT4 expression regulates multiple signalling pathways, including p38 mitogen-activated protein kinase (MAPK)/caspase-3, Wnt/β-catenin, AKT, and Janus Kinase (JAK)/signal transducer and activator of transcription (STAT)3 signal pathways, thereby resulting in the promotion of tumorigenesis and malignant transformation, and increase of recurrences. 26 27 28 29 …”
Section: Discussionmentioning
confidence: 99%
“…Considering the many functions of mTOR, such as sensing metabolic changes, these results and studies implicate HSF1 in many functions of cancer cell biology and a significant interplay between PI3K/AKT signaling, mTOR signaling, and HSF1 activity. Other studies have shown that targeting OCT4 [ 40 ], p70S6K [ 41 ], MAP kinase components [ 42 , 43 ], IGF-1R [ 44 ], and HER2 [ 45 ] may also be co-targets of PI3K/AKT that show efficacy. Our results indicate another molecular in HSF1 that could also be a potential co-target with PI3K/AKT.…”
Section: Discussionmentioning
confidence: 99%